Monitoring and evaluation practices of volunteer tourism organisations. Issue 11 (2nd November 2017) - Steele, Jessica; Dredge, Dianne; Scherrer, Pascal
ABSTRACT: Monitoring and evaluation are tools that can facilitate sustainable and responsible tourism planning and management in organisations through encouraging good practice and the continuous improvement of programmes. However, to date, there is limited knowledge and understanding of how, or indeed if, volunteer tourism organisations actually monitor and evaluate their programmes. The aim of this paper is to identify and critically examine the extent to which volunteer tourism organisations engage with the monitoring and evaluation of their projects. Based on a survey of 80 organisations and qualitative interviews with representatives from 29 organisations, the research found that monitoring and evaluation practices vary greatly. Participants readily accept a lack of time and resources as barriers to monitoring an evaluation, there is an assumption that any volunteer-host community interaction is positive, and despite voluntary guidelines, there is little incentive to prioritise monitoring and evaluation of volunteer programmes. A small number of volunteer organisations emerged as an exception to this overall pattern and are discussed. Discrepancies between stated importance of monitoring and evaluation and actual practices are examined and opportunities for improved practices identified.